An unusually severe Case of dermatosis neglecta: a diagnostic challenge - Pérez Rodríguez, Irma Margarita; Muñoz Garza, Fania Zamantta; Ocampo Candiani, Jorge (2014)
Dermatosis neglecta is a condition secondary to lack of cleanliness, characterized by the formation of hyperkeratotic plaques located in a particular region of the body, usually due to a disability, and it is considered a diagnostic challenge because it can mimic other entities. We present the case of an 18-year-old woman with a 2-month history of progressive brown verrucous plaque in her face. Our first impression was seborrheic dermatitis and she was treated with facial cleanser soap and topic hydrocortisone 1%. One month later, she arrived with new lesions. Because of this our diagnosis changed to Darier’s disease versus seborrheic pemphigus versus foliaceus pemphigus. Histopathology and immunofluorescence studies were compatible with seborrheic dermatitis. The patient complained of depression and social withdrawal and denied facial cleansing. Facial cleansing was performed during consultation presenting resolution of the lesions, which confirmed the diagnosis of dermatosis neglecta. Dermatosis neglecta is a disease that can be frequently misdiagnosed, since it has many differential diagnoses, such as hyperkeratotic syndromes. It should be recognized early and aggressive diagnostic and therapeutic methods should be avoided.